Readability of Patient Education Materials From High-Impact Medical Journals: A 20-Year Analysis. (28th February 2021) - Rooney, Michael K; Santiago, Gaia; Perni, Subha; Horowitz, David P; McCall, Anne R; Einstein, Andrew J; Jagsi, Reshma; Golden, Daniel W
Comprehensive patient education is necessary for shared decision-making. While patient–provider conversations primarily drive patient education, patients also use published materials to enhance their understanding. In this investigation, we evaluated the readability of 2585 patient education materials published in high-impact medical journals from 1998 to 2018 and compared our findings to readability recommendations from national groups. For all materials, mean readability grade levels ranged from 11.2 to 13.8 by various metrics. Fifty-four (2.1%) materials met the American Medical Association recommendation of sixth grade reading level, and 215 (8.2%) met the National Institutes of Health recommendation of eighth grade level. When stratified by journal and material type, general medical education materials from Annals of Internal Medicine were the most readable ( P < .001), with 79.8% meeting the eighth grade level. Readability did not differ significantly over time. Efforts to standardize publication practice with the incorporation of readability evaluation during the review process may improve patients' understanding of their disease processes and treatment options.